Health of the individual, of the family, of society - The Pioneer Health Foundation (Social Medicine Publication Group, 2024)
Twenty-one years ago the Pioneer Health Centre housing the Peckham Experiment, closed. During twelve working years it explored the nature of health and had devised a method for its scientific investigation. Since that time the particular contribution the experiment made to the knowledge of health has not been further developed on.a laboratory scale. But there has been published a statement of the underlying hypothesis which determined the scope of its experimental approach to health.1 This hypothesis opens up a wealth of possibilities for future research and exploration. It is our belief that the times are such that the search for health is a first priority and that it is therefore urgent that this study should be resumed. The following pages give a very brief description of some features of the original experiment. The field is that of health:- of the individual, of the family, of society.